RECONSTRUCTION OF ISLAMIC RELIGIOUS EDUCATION BASED ON RELIGIOUS MODERATION: A CONCEPTUAL STUDY FROM THE PERSPECTIVE OF CONTEMPORARY ISLAMIC EDUCATION - Puji Astutik; Syaiful Hadi (FAJAR Jurnal Pendidikan Islam, 2026)
Islamic Religious Education (PAI) plays a strategic role in shaping students’ religious character within the context of Indonesia’s plural society. Current challenges such as the rise of religious extremism, social polarization, and widespread misconceptions about Islamic teachings exacerbated by digital media demand a comprehensive educational framework that fosters religious moderation. This study aims to construct a conceptual model of PAI learning based on religious moderation by examining the Islamic principles of wasathiyah, reconstructing curriculum content, identifying supportive pedagogical approaches, clarifying the teacher’s role, and synthesizing these elements into a coherent theoretical framework. This research employs a qualitative design using a library research approach. Data were collected from classical Islamic texts, contemporary scholarly works, official policy documents, and relevant academic articles. The analysis was conducted through data reduction, thematic categorization, and theoretical synthesis using content analysis techniques. The study focuses on conceptual development rather than empirical testing. The findings reveal that the principles of religious moderation—including justice, balance, tolerance, and anti-extremism—are firmly rooted in Islamic teachings and serve as essential foundations for PAI instruction. The PAI curriculum needs to be reconstructed to become more inclusive, contextual, and grounded in diverse Islamic scholarly traditions in order to cultivate comprehensive religious understanding. Pedagogically, dialogic, reflective, collaborative, and experiential learning approaches are effective in fostering moderate religious awareness among students. Teachers function not only as knowledge transmitters but also as moral exemplars, facilitators, and agents of moderation who shape the school’s religious climate. These four domains are synthesized into a conceptual model for PAI instruction that encompasses foundational values, curriculum reconstruction, pedagogical strategies, teacher roles, and supportive learning environments.